Variations in temperature‐related extreme events (1975–2014) in Ny‐Ålesund, Svalbard. (28th October 2015) - Wei, Ting; Ding, Minghu; Wu, Bingyi; Lu, Changgui; Wang, Shujie
Abstract: We present a comprehensive analysis of temperature‐related extreme events in Ny‐Ålesund (78.9°N, 11.9°E) using data from three meteorological stations. The results show that annual mean temperatures in Ny‐Ålesund increase at a rate that is four times faster than the global mean from 1975 to 2014 with no 'hiatus' in recent decades. The annual diurnal temperature range shows a negative trend as minimum daily temperature increases at a faster rate than maximum daily temperature. A negative trend in cold extremes and a positive trend in warm extremes are observed. This asymmetry hints at potential changes in the probability distribution of temperatures in Ny‐Ålesund.